Making tools, Reconstructing Manufacturing Processes: The Celt Industry of Varemeni Goulon in Northern Greece - Stroulia, Anna (Journal of Greek Archaeology, 2018)
Of all macrolithic types known from Neolithic Greece, cutting edge tools, or celts as they are widely known, have attracted most archaeological attention. This emphasis is certainly not explained by math. Celts have been studied more intensely, even though their numbers rarely exceed those of other macrolithic types (e.g. grinding tools). Other less straightforward factors are probably responsible - the disciplinary traditions in which we scholars operate and our aesthetic priorities, for example.